Analisis Perbedaan Pendapatan Pengerajin Tenun Sebelum dan Sesudah Adanya Ritel Modern - Lalu Reza Wisnu Winata; Zainal Arifin; Sudarti (Jurnal Ilmu Ekonomi, 2021)
The background of this research is that there is a gap between regions that is a serious problem, the gap affects the income of artisans in sukarara village with modern retail entrepreneurs. Based on the background of this research, the purpose of this research is to know the characteristics of weaving entrepreneurs and to know if there are differences in the income of weaving craftsmen before and after the arrival of modern retail in Sukarara Village Jonggat District central Lombok Regency. main objective of this study is to analyze the characteristics and the effect of the modern retail market on the difference of income level to weave production in Sukarara Village, Lombok Tengah Regency in one month. The method in this research is quantitative descriptive, that is analyzed of the different test (t-test) using the SPSS application. The data used are primary, primary data obtained through field interviews directly to weaving craftsmen on Sukarara Village. From the results of the study, it can be concluded that there are significant income differences obtained by weaving entrepreneurs after and before the existence of modern weaving retail. Changes in income in the form of a decrease in income occur on average by Rp. 1,775,862 of all respondents.